INTERNET AND CROSS-CULTURAL COMMUNICATION TO GENERATION Z - Andryani Sihombing, Indah; Mono, Umar; Perangin-angin, Alemina Br. (Linguistik : Jurnal Bahasa dan Sastra, 2022)
Generation Z can be regarded as a generation that since they were born have grown up with the internet. The digital generation's reliance on information and communication technologies in both personal and professional affairs may be at an all-time high. Because they are "technologically proficient," they have some competitive advantages over previous generations. As a result, Gen Zers are prepared and motivated to work in a multicultural business environment, contributing to the advancement of globalization and interconnection. Without a doubt, in today's environment, the transformation of the global workforce is the most globally oriented. With globalization and technology continuing to have an impact, Gen Zers' way of thinking supports cross-cultural social engagement and communication, making bridge leadership skills and strategies increasingly more crucial for CEOs of large and small businesses.